Aid and the Resource Curse : How Can Aid Be Designed to Preserve Institutions? - Harford, Tim; Klein, Michael (World Bank, Washington, DC, 2012)
Many studies have found that countries with abundant natural resources grow more slowly than those without a phenomenon often known as the resource curse or the curse of oil. Some development specialists are concerned that foreign aid may also cause a resource curse. Recent research is not conclusive, but certainly does not rule out the possibility. This Note suggests ways to avoid this risk and urges more attention be devoted to it.